2009
DOI: 10.1016/j.neuroscience.2009.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory grip force control using a cerebellar model

Abstract: Abstract-Grip force modulation has a rich history of research, but the results remain to be integrated as a neurocomputational model and applied in a robotic system. Adaptive grip force control as exhibited by humans would enable robots to handle objects with sufficient yet minimal force, thus minimizing the risk of crushing objects or inadvertently dropping them. We investigated the feasibility of grip force control by means of a biological neural approach to ascertain the possibilities for future application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Sequence learning studies commonly describe extensive decreases in motor and cerebellar cortex, as well as frontal and parietal regions, as learning progresses Doyon, 2002, 2005;Floyer-Lea and Matthews, 2004;Lehéricy et al, 2005), and the model proposed by Doyon and Benali (2005) predicts decreases in most areas of the learning network. Decreases in M1 have been detected early in learning (Karni et al, 1995;Floyer-Lea and Matthews, 2004) and have been attributed to habituation or repetition suppression (Grill-Spector et al, 2006), whereas cerebellar cortical decreases have been interpreted as the decreased need for error correction as learning progresses (Ito, 2000;Penhune and Doyon, 2005;de Gruijl et al, 2009). The global decreases identified in our study are sharply contrasted by increases in specific subregions of M1 and cerebellar cortex.…”
Section: Global Decreases With Specific Increasessupporting
confidence: 43%
“…Sequence learning studies commonly describe extensive decreases in motor and cerebellar cortex, as well as frontal and parietal regions, as learning progresses Doyon, 2002, 2005;Floyer-Lea and Matthews, 2004;Lehéricy et al, 2005), and the model proposed by Doyon and Benali (2005) predicts decreases in most areas of the learning network. Decreases in M1 have been detected early in learning (Karni et al, 1995;Floyer-Lea and Matthews, 2004) and have been attributed to habituation or repetition suppression (Grill-Spector et al, 2006), whereas cerebellar cortical decreases have been interpreted as the decreased need for error correction as learning progresses (Ito, 2000;Penhune and Doyon, 2005;de Gruijl et al, 2009). The global decreases identified in our study are sharply contrasted by increases in specific subregions of M1 and cerebellar cortex.…”
Section: Global Decreases With Specific Increasessupporting
confidence: 43%
“…Learning was proposed to occur as long-term synaptic plasticity at the parallel fiber - Purkinje cell synapses in the form of long-term depression under instructive control by climbing fibers. Simulations carried out with these models suggested that a control scheme incorporating cerebellum adaptation played indeed a critical role for point-to-point arm movement and for prism glasses compensation in throwing at a target [11], [12], for anticipatory grip force modulation [13], and for Pavlovian collision avoidance [14]. While computational simulations guarantee repeatability over trials and therefore a systematic evaluation of the control scheme, testing with real robots is needed to assess the robustness and generalizability of models in closed-loop conditions, in which unwanted perturbations disturb learning and control.…”
Section: Introductionmentioning
confidence: 99%
“…However, good results obtained in one specific task rarely carry over to another task without extensive tweaking of the model. For instance, a model that adequately learns the dynamics of a robot arm even without tight timing of error signals (Spoelstra et al 2000) may perform worse on a seemingly simpler task and require much tighter timing of error signals (De Gruijl et al 2009). Due to this inter-task variability and the necessity of task-specific tweaking of the model, the outcomes of large-scale models by themselves can be hard to interpret.…”
Section: Functional Models Of the Olivocerebellar System Marr-albus-imentioning
confidence: 99%